Physical, Chemicals and Flavors of Some Varieties of Arabica Coffee - Yusianto .; Retno Hulupi; Sulistyowati .; Cahya Ismayadi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2005)
Export of Arabica coffee was 28,100 tons/year or 8.28% total export of Indonesian coffee, most of them are specialty coffee. Beside their origin, variety and determine the of physical, chemical and flavors characters. The promising clones or varieties i.e. BP 416A, BP 418A, BP 430A, BP 431A, BP 432A, BP 507A, BP 508A, BP 509A, BP 511A, BP 513A, BP 516A, BP 517A and BP 518A still not be determined their quality This research was conducted to analyze their physicals, chemicals and flavors during 2 periods of harvesting (2004 and 2005), using AS 1, S 795 and USDA 762 as the control. Mature coffee berry was harvested, sorted manually, and depulped, cleaned manually and then fermented in plastic sacks during 36 hours. The fermented parchment was washed, and then sun dried, dehulled to get green coffee. Observations wre conducted on green coffee yield, husk content, color of green coffee, distribution of size, bulk density of green and roasted coffee, roasting characters, color of roasted beans, and pH, acidity and flavors. The results showed (a) The lowest content of husk was BP 432A and the highest was USDA 762. The control varieties of AS 1, S 795 and USDA 762, showed husk content >15%, while those potential varieties were < 15% except BP 416A. (b) Beans size >6,5 mm and more than 80% were BP 416A, BP 430A, BP 432A, BP 509A, P 88 and S 795. Green coffee of BP 430A, BP 432A and BP 509A were uniform, but S 795 was not uniform. AS 1 and BP 416A and P 88 was one group; S 795 was one group with BP 542A; BP 509 was a group with BP 432A; but BP4 30A and USDA 762 were the other groups. (c) Green coffee of USDA 762 was the palest color, but BP 542A was the darkest color. AS 1 and S 795 were a group with all potential varieties, except BP 542A. (d) Roasted coffee of USDA 762 was the palest color and AS 1 was the darkest. In this case, AS 1 was a group with BP 430A, BP 509A and P 88, while S 795 was a group with BP 416A and BP 432A, but USDA 762 and BP 542A were the other groups. (e) The lowest pH and the highest acidity was AS 1. In this case, S 795, BP 416A, BP 509A, BP 430A, P 88, BP 542A, AS 1 and BP 542A were one group, but USDA 762 was the other group. (f) Bulk density of all observed varieties were >0.7 for green coffee and 0,39–0,47 for medium roasted coffee. (g) Outurn of all observed varieties were >83% and volume increment >50%, except for USDA 762. (g) AS 1 showed the best flavor characters, while USDA 762 was the lowest. The promising varieties which showed a group with AS 1 were P 88 and BP 542A, which fruity. All of tested varieties showed green flavor. Harsh flavor was found in BP4 16A, BP 509A, P 88, S 795 and USDA 762. (h) Based on the physicals, chemicals and flavors characters, 202 AS 1 was a group with P 88 and BP 542A; S 795 a group with BP 416A, BP 430A, BP 432A and BP 509, while USDA 762 was other group. Key words:Coffee, physic, chemical, flavor, variety.